THE RELATIONSHIP BETWEEN STAND WORK ATTITUDE AND WORK FATIGUE IN EMPLOYEES OF PT. SENTRALINDO TEGUH GEMILANG II - Subiyanto Subiyanto; Bernard Hasibuan Hasibuan; Soehatman Ramli (Jurnal Scientia, 2022)
Protection for good workers is increasingly real, this is aimed at increasing the standard of living for a better life. In applications in industrial society, it is hoped that it will be able to provide a balance between the tools used and their impacts. The standing work attitude of workers is always moving to always adjust to the condition of the body. This condition is to avoid constant pressure on their spine and legs. Incompatibility of body conditions This will impede blood flow due to accumulation of blood under the body. This study uses an associative explanatory quantitative method used in this type of research. The quantitative method can also be said to be a research method in which its application starts from the collection, analysis, presentation and conclusions related to quantitative data. The results of this study prove that one researcher with another has the opposite conclusion, so the researcher wants to try to retest the model that affects work fatigue. There is a relationship between standing work attitude towards work fatigue and standing work attitude has a positive effect on work fatigue so that it has implications for increasing musculoskeletal complaints with standing work attitude also increasing the level of work fatigue.